Expert System For Diagnosing Diseases In Children Under Five Uses Certainty Factor Based Websites - Faiqotul Himma Ramadhanti; Ade Eviyanti (Universitas Muhammadiyah Sidoarjo, 2021)
Immunity in children under five is not as good and perfect as adult immunity. Therefore, children under five are susceptible to disease and easily contracted by adults. Lack of knowledge about the symptoms of a disease that attacks children under five can aggravate the situation and result in delays in treatment by medical personnel. Therefore, this expert system is made to make it easier for parents to recognize the symptoms of diseases that attack their toddlers. With this expert system, parents can find out the early symptoms of the disease that attacks their child. In making this expert system using a certainty factor method or a method that defines the measure of certainty of facts or rules to describe an expert's belief in the problem at hand. This expert system will diagnose the symptoms that the patient has previously selected. Then from the choice of these symptoms will be obtained using the value of expert confidence that has been stored in the knowledge. The results of this study were to build an expert system for diagnosing diseases in children under five using a certainty factor method based on a website. With this website, we can take advantage of today's technology to diagnose diseases in children under five. This website can make it easier for parents to consult because they can use it anywhere, effectively and quickly.